Factors Associated With The Assessment Of Maternal Participant Satisfaction Of BPJS Health In The Working Area Of Public Health Center Lubuk Buaya Padang City 2017 - Rahmayani Afrah; Defrin Defrin; Ayu Nurdiyan (Journal of Midwifery, 2017)
Satisfaction is someone’s level of approval when comparing perceived performance or result with his or her expectation. Satisfaction assessment aims to determine the quality of a service. Based on the preliminary survey, Lubuk Buaya Public Health Center has the largest number of BPJS Health participants in Padang, but the scope of maternity gets decreased. This study seeks to investigate the relevant factors that influence the satisfaction assessment of BPJS Health participants with maternity services in the working area of Lubuk Buaya Public Health Center in Padang in 2017.This study was quantitative research with cross sectional design and was conducted in the working area of Lubuk Buaya Public Health Center from May to July 2017. Sample of this research were 75 puerperal mothers. Data were collected by using questionnaire. Data analysis was performed by using univariate and bivariate.The results showed that there are 26 dissatisfied respondents (34.7%) and 49 satisfied respondents (65.3%). Based on the analysis of maternal satisfaction level, the satisfaction of BPJS Health participants in the working area of Lubuk Buaya Public Health Center was 76.13%. The result of bivariate analysis showed that there was no correlation between participants’ age (p=0,198), membership of BPJS Health (p=0,961), and previous service (p = 0,673), but there was a correlation between education (p=0,001), employment (p=0,001) and parity (p=0,035) with assessment of BPJS Health participants in working area of Lubuk Buaya Public Health Center in Padang in 2017.There was a correlation between education, employment, and parity with the assessment of BPJS Health participants who got maternity services. Therefore, health workers have to do evaluation about  the maternity services in order to improve maternity satisfaction of BPJS Health participants.